1996
DOI: 10.1073/pnas.93.8.3428
|View full text |Cite
|
Sign up to set email alerts
|

Calpain inhibitor AK295 attenuates motor and cognitive deficits following experimental brain injury in the rat.

Abstract: Marked

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
0
10

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(143 citation statements)
references
References 52 publications
6
127
0
10
Order By: Relevance
“…Bartus and colleagues 6 , who investigated the effect of AK 295 in a model of focal ischemic brain damage, showed that the intra-arterial administration of that molecule protected neurons from ischemia. Saatman and colleagues 36 investigated the efficacy of AK 295 in a murine model of experimentally induced traumatic injury. Those investigators showed that calpain has a role in posttraumatic events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bartus and colleagues 6 , who investigated the effect of AK 295 in a model of focal ischemic brain damage, showed that the intra-arterial administration of that molecule protected neurons from ischemia. Saatman and colleagues 36 investigated the efficacy of AK 295 in a murine model of experimentally induced traumatic injury. Those investigators showed that calpain has a role in posttraumatic events.…”
Section: Discussionmentioning
confidence: 99%
“…AK 295, which is considered to be an antiapoptotic agent that counteracts the effects of calpains, has been reported to have a role in the treatment of a variety of pathologic CNS conditions (including trauma and brain ischemia) induced in an experimental setting 6,36 . They showed that AK 295 provided significant neuroprotection of brain tissue and attenuated motor and cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Although calcium effects are so widespread that it has been difficult to define specific mechanisms, intracellular increase of calcium elicits diverse pathological effects through cell death in cerebral ischemia and other neural insults including glutamate, kainite, maitotoxin, and brain trauma, and neurodegenerative processes such as Alzheimer's disease (2,5,6,(35)(36)(37)(38). A wide range of stimuli eliciting apoptotic cell death acts through elevations in intracellular calcium and activations of calpain.…”
Section: Discussionmentioning
confidence: 99%
“…These earlier observations have led to the hypothesis that calpains play an important role in modulating cellular structure in both normal and pathological states. For example, increased calpain activation has been associated with neuronal degeneration caused by traumatic events such as excitotoxicity and hypoxia/ischemia (Kampfl et al, l996a;Yamashima et al, 1996), and various calpain inhibitors such as calpain inhibitor I, calpain inhibitor II, leupeptin, MDL-28 170, and A295 prevented insult-induced neuronal degeneration in both animal (Bartus et al, 1994;Kampfl et al, 1996b;Saatman et al, 1996) and neuronal cell culture models (Brorson et al, 1995; for review, see Wang and Yuen, 1994). In contrast, calpain activity has been shown to play a role in the recovery of neuronal cell structure after cytotoxic insults (Faddis et al, 1997) and is postulated to contribute to neuronal plasticity (Vanderklish et al, 1996) and modification of synaptic function (Dosemeci and Reese, 1995).…”
Section: Discussionmentioning
confidence: 99%